Hubungan Antara Administrasi Kualitas dan Manajemen Kualitas dalam Konteks Peningkatan Mutu Pembelajaran Bahasa Jerman di SMA Negeri 17 Maluku Tengah - Henderika Serpara; Patresia Apituley; Eldaa Crystle Wenno (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aimed to analyze the level of quality administration, the level of quality management in German language learning, and the relationship between the two variables at SMA Negeri 17 Maluku Tengah. The study employed a quantitative approach with a descriptive-correlational design. The respondents consisted of 20 participants selected through total sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and Pearson Product-Moment correlation. The results showed that quality administration was categorized as very high, with an achievement percentage of 91.4%, while the quality management of German language learning was also categorized as very high, with an achievement percentage of 97.0%. The highest indicator of quality administration was data accuracy, whereas the highest indicators of quality management in German language learning were the implementation of instruction and follow-up for quality improvement. The correlation test revealed a positive and significant relationship between quality administration and the quality management of German language learning (r = 0.461; p = 0.041). These findings indicate that quality administration plays an important role in supporting more effective management of German language learning quality